Islamic Business Ethics in Corporate Management Through the Application of Sharia Principles - Sugandi, Dede; Kuswandi, Sony; Yudianto, Yosep; Surya, Candra Mochamad; Sudirman, Dhani (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Modern business practices face challenges in maintaining a balance between profit orientation and ethical values, thus requiring an approach capable of integrating moral aspects into corporate management. From an Islamic perspective, business ethics not only serves as a normative guideline but also as an operational foundation that regulates economic behavior as a whole. This study aims to analyze the application of Islamic business ethics in corporate management through sharia principles at NU Mart Karawang. The method used is a qualitative approach with a case study type, with data collection techniques including interviews, observation, and documentation. The data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing, in order to systematically interpret the findings. The results show that the application of Islamic business ethics has been realized in operational practices through the values of honesty, fairness, and responsibility, and is supported by the company's social orientation. However, this implementation has not yet been fully integrated into a formal and structured management system. Thus, it can be concluded that the application of Islamic business ethics at NU Mart Karawang has been running substantively in practice, but still requires strengthening in aspects of the management system to be more structured and sustainable. The implications of this study emphasize strengthening sharia-based management systems through clear SOPs and structured supervision, so that ethical values can be implemented consistently and support sustainable business practices.